2019
DOI: 10.3390/jcm9010008
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilicity of Bacteriochlorin-Based Photosensitizers as a Determinant for PDT Optimization through the Modulation of the Inflammatory Mediators

Abstract: Photodynamic therapy (PDT) augments the host antitumor immune response, but the role of the PDT effect on the tumor microenvironment in dependence on the type of photosensitizer and/or therapeutic protocols has not been clearly elucidated. We employed three bacteriochlorins (F 2 BOH, F 2 BMet and Cl 2 BHep) of different polarity that absorb near-infrared light (NIR) and generated a large amount of reactive oxygen species (ROS) to compare the PDT efficacy after various drug-to-light intervals: 15 min. (V-PDT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 71 publications
(166 reference statements)
0
24
0
Order By: Relevance
“…Previous research found that some drugs could efficiently elevate the aPDT efficacy and cellular uptake of PS by increasing cell membrane permeability (34,35). In our study, DHA was used to play the roles mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that some drugs could efficiently elevate the aPDT efficacy and cellular uptake of PS by increasing cell membrane permeability (34,35). In our study, DHA was used to play the roles mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to traditional treatment methods, PDT has laid a solid foundation for its clinical application due to its weak invasiveness, ideal convenience and flexibility, effective efficacy, and high acceptance of patient [103]. In addition, due to the lack of effective PS, appropriate light doses, and effective PS delivery, there are still many limitations to PDT as a first-line clinical treatment.…”
Section: Pdt Of Cancermentioning
confidence: 99%
“…Moreover, (N-methylpyridinium-4-yl)-substituted PSs are also known from their direct binding to DNA [ 38 ]. The porphyrin ring modifications are undertaken to modulate both the redox properties and change the physicochemical features, charge distribution, and lipophilicity [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%